2021
DOI: 10.3233/faia210080
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Personalized Fully Immersive Virtual Reality Learning Environments with Gamified Design in Education

Abstract: Traditional learning methods frequently fail to provoke students’ interest, stimulate their enjoyment and encourage them to participate in learning activities, resulting in discomfort, distractions, and disengagement, if not quitting. Education’s goal is to improve the quality and effectiveness of teaching and learning methods. This paper aims to present a framework based on Virtual Reality (VR) technology and contemporary Head Mounted Displays, that incorporates game-based techniques and adaptive design accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 27 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…Students were able to manipulate virtual molecular models, participate in simulated chemical experiments, and explore complex concepts through hands-on interaction. This interactivity facilitated experiential learning, allowing students to internalize abstract ideas by actively interacting with them [10]. The immersive aspect of VR resonated with students as it provided a more tangible and memorable learning experience compared to traditional methods.…”
Section: Interactivity and Experiential Learningmentioning
confidence: 99%
“…Students were able to manipulate virtual molecular models, participate in simulated chemical experiments, and explore complex concepts through hands-on interaction. This interactivity facilitated experiential learning, allowing students to internalize abstract ideas by actively interacting with them [10]. The immersive aspect of VR resonated with students as it provided a more tangible and memorable learning experience compared to traditional methods.…”
Section: Interactivity and Experiential Learningmentioning
confidence: 99%
“…Numerous efforts have been undertaken to explore, study, and harness the potential of virtual platforms [5]. The utilisation of virtual platforms allows students to engage in curriculum-related experiments and procedures that may otherwise be excessively costly, dangerous, or unfeasible [6]. The transition between physical and virtual classrooms has prompted innovative endeavours to enhance the teaching environment, adapting to the changes and contradictions that arise [7].…”
Section: Related Workmentioning
confidence: 99%
“…Amidst the popularity of VR, it has been employed as a teaching tool. Marougkas et al [6] devised a framework for personalized VR learning environments to enhance gamified educational experiences. Zhang and Liu's study [10] identified the immersive potential of VR as an advantage over traditional physical methods within pedagogy.…”
Section: Related Workmentioning
confidence: 99%
“…The oral aspect of mobile learning has been noted as particularly important [1]. Digital games and other technologies have also been used to enhance learning, such as Troussea et al's mobile language learning application with a chatterbot, MACE: a mobile artificial conversational entity for adapting domain knowledge and generating personalized advice [2][3][4], and Marougkas' framework for personalized virtual reality learning environments [5]. Studies have shown that students prefer instant messaging as a communication tool [6], and a survey of college students revealed they spend nearly 6 h a day on their smartphones [7].…”
Section: Introductionmentioning
confidence: 99%